Z-Propaganda and Semiotic Resistance: Contesting Russia’s War Symbols in Moldova and Beyond - Marandici Ion (Comparative Southeast European Studies)
This article examines the range of strategies adopted by various states vis-à-vis the symbols of the Russian war against Ukraine—the St. George ribbon and the letters Z and V. First, it analyzes their genealogy, illustrating how the St. George ribbon reflects Russia’s new authoritarian-imperial identity, while the Z and V originate from ultranationalist Telegram communities promoting white supremacist and genocidal ideas. Second, the concept of semiotic resistance is proposed to explain how states and societies counter Russia’s pro-war narratives by implementing diverse semiotic strategies. Finally, the in-depth analysis of the identity politics accompanying the symbolic ban in Moldova reveals how competing definitions of nationhood lead to divergent assessments of Russia’s war narratives. The dispute over the St. George ribbon in Moldova is embedded in longstanding domestic culture wars, fought in the legal-political domain as well as in urban spaces.